High‐flow nasal cannula vs standard respiratory care in pediatric procedural sedation: A randomized controlled pilot trial. Issue 10 (29th July 2020) - Klotz, Daniel; Seifert, Viktor; Baumgartner, Jana; Teufel, Ulrike; Fuchs, Hans
Abstract: Introduction: Respiratory instability is frequently observed during pediatric procedural sedation. The aim of this trial was to estimate the impact of high‐flow nasal cannula (HFNC) therapy on respiratory stability during sedation for upper gastrointestinal tract endoscopy in children. Methods: Prospective randomized controlled non‐blinded single‐center pilot trial. Children were randomly allocated to receive either HFNC (2 L/kg/min) or low‐flow nasal oxygen cannula (LFNC, standard care). FiO2 was titrated to maintain SpO2 94% to 98% in both groups. Primary outcome was the number of events of respiratory instability defined by prespecified criteria (hypoxia, hypercapnia, apnea). Secondary outcomes included type and duration of events, number of interventions to regain respiratory stability and cumulative doses of medication. Results: Fifty children (mean age, 12.3 ± 3.1 years) were enrolled and treated with HFNC (n = 25) or LFNC (n = 25). Patient and intervention characteristics were not different in the two study groups, including total oxygen flow rate. Mean (SD) number of respiratory events in the HFNC group was 2.0 ± 1.9 events compared to 2.0 ± 1.4 events in the LFNC group ( P = .65; 95% CI of difference, −1.0 to 1.0). There was no difference for any secondary outcome criteria, percentage of patients for any outcome criteria and no difference in the number of respiratory events or airway management maneuvers per patient between treatment groups. Conclusions: HFNC did not increase respiratory stability in sedated children undergoing upper gastrointestinal tract endoscopy compared to LFNC.